IMPLEMENTASI METODE ACTIVITY BASED COSTING TERHADAP PERHITUNGAN BIAYA PRODUKSI TEMPE PADA USAHA MIKRO “DUA PUTRI“ KELURAHAN BAKUNASE KOTA KUPANG - Ana Yunita. K Muda; Sondang S. P. Pudjiastuti; Yacobus C. W. Siubelan; Tomycho Olviana (Undana Press, 2023)
This study aims to implement the Activity Based Costing (ABC) method in calculating production costs because it can provide more accurate cost-related information and become a reference for determining selling prices using the Cost Plus Pricing method and calculating profits in the